Transcranial Direct Current Stimulation on the Left Superior Temporal Sulcus Improves Social Cognition in Schizophrenia: An Open-Label Study - Yamada, Yuji; Sueyoshi, Kazuki; Yokoi, Yuma; Inagawa, Takuma; Hirabayashi, Naotsugu; Oi, Hideki; Shirama, Aya; Sumiyoshi, Tomiki (Frontiers in Psychiatry, 2022)
Backgrounds: Patients with schizophrenia show impairments of social cognition, which cause poor real-world functional outcomes. Transcranial direct current stimulation (tDCS) delivered to frontal brain areas has been shown to partially alleviate disturbances of social cognition. In this study, we aimed to determine whether multi-session tDCS targeting the superior temporal sulcus (STS), a brain region closely related to social cognition, would improve social cognitive performance in patients with schizophrenia. Methods: This was an open-label, single-arm trial to investigate the benefits and safety of multi-session tDCS over the left STS. Fifteen patients received tDCS (2mA×20min) two times per day for 5 consecutive days. Anodal and cathodal electrodes were placed over the left STS and right supraorbital regions, respectively. Assessments with the Social Cognition Screening Questionnaire, Hinting Task, Brief Assessment of Cognition in Schizophrenia, and Positive and Negative Syndrome Scale, were conducted at baseline and 1 month after the final stimulation. Results: Significant improvements were found on theory of mind, as measured using the Social Cognition Screening Questionnaire (d = 0.53) and Hinting Task (d = 0.49). These changes on social cognition were not correlated with those of neurocognition, as measured using the Brief Assessment of Cognition in Schizophrenia, or psychotic symptoms, as measured using the Positive and Negative Syndrome Scale. There were no adverse events of serious/moderate levels attributable to tDCS. Conclusions: These results suggest that administration of multi-session tDCS with anode stimulation targeting the left STS provides a novel strategy to improve functional outcomes in patients with schizophrenia. Ethics statement: National Center of Neurology and Psychiatry Clinical Research Review Board (CRB3180006) approved this study. Trial registration: This study was registered within the Japan Registry of Clinical Trials (jRCTs032180026).